Gait Impairment and Upper Extremity Disturbance Are Associated With Total Magnetic Resonance Imaging Cerebral Small Vessel Disease Burden - Hou, Yutong; Li, Yue; Yang, Shuna; Qin, Wei; Yang, Lei; Hu, Wenli (Frontiers in Aging Neuroscience, 2021)
ABSTRACT Background and Purpose: Cerebral small vessel disease (cSVD), including white matter hyperintensities (WMHs), cerebral microbleeds (CMBs), lacunes and enlarged perivascular spaces (EPVS), is related to gait impairment. However, the association between the total magnetic resonance imaging (MRI) cSVD burden and gait and upper extremity function remains insufficiently investigated. This study aimed to assess the correlation between the total MRI cSVD burden score and gait impairment as well as upper extremity impairment. Method: A total of 224 participants underwent MRI scans, and the presence of lacunes, WMHs, CMBs, and EPVS was evaluated and recorded as a total MRI cSVD burden score (range 0–4). Gait was assessed by 4-m walkway, Tinetti, Timed Up and Go (TUG) and Short Physical Performance Battery (SPPB) tests. Upper extremity function was assessed by 10-repeat hand pronation-supination time, 10-repeat finger-tapping time and 10-repeat hand opening and closing time. Result: The mean age of the 224 participants was 60.6±10.5 years, and 64.3% were men. Independent of age, sex, height and vascular risk factors, multivariable linear regression analyses showed that a higher total MRI cSVD burden score was related to a shorter stride length, wider step width, higher cadence and poorer performance on the Tinetti, TUG and SPPB tests and upper extremity tests (all P <0.05). Conclusion: Total MRI cSVD burden was associated with gait impairment and upper extremity disturbances, suggesting that total MRI cSVD burden might contribute to motor function decline. Longitudinal studies are required to determine whether there is a causal relationship between total MRI cSVD burden and motor function decline.